P03.02 Ketogenic diets as an adjuvant therapy in glioblastoma (KEATING): A mixed method, randomised, feasibility study. (19th September 2018) - Martin-McGill, K J; Cherry, M G; Marson, A G; Tudur Smith, C; Jenkinson, M D
Abstract: Background: There is increasing interest in the use of ketogenic diets (KD) as adjuvant therapy for glioblastoma (GBM). This trial aimed to: (i) investigate protocol feasibility, (ii) measure patient and carer tolerability and (iii) inform the design of future phase III clinical trials. Material and Methods: A prospective, non-blinded, randomised, feasibility study with an embedded qualitative design assessing recruitment and retention challenges and experiences. Twelve newly diagnosed GBM patients were randomised to the modified ketogenic diet (MKD) or the medium chain triglyceride ketogenic diet (MCT KD). Primary outcome was retention at 12 weeks. Secondary outcomes assessed at 12 weeks and 12 months included recruitment rate, side effects, anthropometric changes, dietary acceptability and long term retention. Semi-structured interviews were conducted with a purposive sample of patients and relatives (n=15), including those who declined, withdrew and retained up until 12 weeks. Results: Recruitment was achieved within the desired timeframe of 12 months. Fifty-seven patients were screened, 42 were eligible to participate and 12 were recruited (29% recruitment rate). Retention was poor; of the 12 patients randomised, 4 completed the 12 week dietary trial, of which 3 followed MCT KD. Median duration on diet was 36.5 days (range 0–49 days) for those who discontinued prior to 12 weeks (n=8). No dietary related serious adverse events occurred. Mean weight loss was 8.51kg (S.D 9.66kg) over 12 weeks (n=4), however this was intentional as all patients were overweight or obese at baseline. Gastrointestinal intolerances occurred at dietary initiation (n=3), resolving by week 6. Those who participated in the study reported their decision to be a 'gut reaction', whilst those who declined to participate appeared more considered in their decision, reporting the diet to be too restrictive and too time consuming for the relative to prepare. Whilst relatives did not influence the patient's decision to participate in the study, all patients sought their relative's opinion. Participants reported high levels of relative burden and support required when implementing KD. Some underestimated this, resulting in withdrawal. Those who withdrew reported KD to negatively impact their lifestyle. Retainers had a positive experience and reported that the diet became 'the new normal'. Ketone monitoring was seen as a motivation for retainers, and a burden for withdrawers. Patients reported that the 3-month diet duration was too long but 5–6 weeks to be more attainable. Conclusion: Recruitment to a GBM ketogenic trial is possible. Retention at 3 months was poor due to the diet negatively impacting patients' lifestyle and causing burden for relatives. To assess efficacy in a stage III trial, a 6 week dietary intervention would be advantageous.